CONTRIBUTION OF GREEN ORIENTATION FOR THE ORGANIZATIONAL PERFORMANCE: A REVIEW OF STAKEHOLDER RELATIONSHIPS AND ECOLOGICAL MODERNIZATION PERSPECTIVES ON SUSTAINABILITY. (October 2018) - Pushpakumara, W. D. Haritha; Atan, Halinah; Khatibi, Ali; Azam, S. M. Ferdous; Tham, Jacquline
No abstract available